(untitled) (East West Medical College Journal, 2024)
Introduction: Premature rupture of membranes (PROM) refers to the breaking of the amniotic sac before the onset of labor. When this happens before 37 weeks of gestation, it is termed preterm (PROM). One critical aspect of managing PROM or PPROM is the microbiological assessment, as infection plays a significant role in the outcome for both mother and fetus. Methods: A prospective cross-sectional study was carried out in a private clinic at Dhaka from January 2023 to December 2023. A total of 50 pregnant patients (N=50) with PROM were enrolled in this study following the inclusive criteria. Data were collected in the predesigned data collection sheet. Data were analyzed statistical package for social science (SPSS). Result: Commonest organism 72% were no growth, 10% were streptococcus, 6% were candida, 2% were delivered alpha-hemolytic streptococcus, 2% were E. coli Conclusion: Premature rupture of membrane and chorioamnionitis may cause antagonistic maternal consequences linked to infection. Premature rupture of membrane indicated lower birth weight for infants. Proper antibiotics must be certain prophylactically for the anticipation of intra-partum infection in case of PROM. EWMCJ Vol. 12, No. 1&2, January-July 2024: 75-79